Prevalence of glaucoma in the Australian National Eye Health Survey. Issue 2 (26th April 2018) - Keel, Stuart; Xie, Jing; Foreman, Joshua; Lee, Pei Ying; Alwan, Mostafa; Fahy, Eamonn T; van Wijngaarden, Peter; Fan Gaskin, Jennifer C; Ang, Ghee Soon; Crowston, Jonathan G; Taylor, Hugh R; Dirani, Mohamed
Abstract : Aim: To estimate the prevalence of glaucoma in Australia. Methods: This was a population-based study of 3098 non-Indigenous Australians (50–98 years) and 1738 Indigenous Australians (40–92 years) stratified by remoteness. Each participant underwent a standard examination that included visual field assessment, tonometry and non-mydriatic fundus photography. Two fellowship-trained glaucoma specialists independently assessed relevant case notes (past ocular history, best-corrected visual acuity, frequency doubling technology visual fields, Van Herick grade, intraocular pressure and optic disc-centred photographs) and assigned a diagnosis ranked on a scale of certainty: none, possible, probable or definite glaucoma. Results: A total of 4792 (99.1%, 3062 non-Indigenous and 1730 Indigenous) participants had retinal photographs in at least one eye that were gradable for glaucoma. The weighted prevalence of glaucoma (definite) in non-Indigenous Australians and Indigenous Australians was 1.5% (95% CI 1.0 to 2.2) and 0.6% (95% CI 0.4 to 1.1), respectively. When definite and probable cases of glaucoma were combined, rates were 3.4% (95% CI 2.7 to 4.3) among non-Indigenous and 1.6% (95% CI 1.1 to 2.3) in Indigenous Australians. Only 52.4% of non-Indigenous Australians and 28.0% of Indigenous Australians with glaucoma self-reported a known history of glaucoma. Conclusion: We estimate that 198 923 non-Indigenous Australians aged 50 years and over and 2139 Indigenous Australians aged 40 years and over have glaucoma. Given the high rates of undiagnosed glaucoma coupled with a significant ageing of the Australian population, improvements in case detection and access to low vision rehabilitation services may be required to cope with the growing burden of glaucoma.